The induction and inhibition of UDP-glycosyltransferases in Haemonchus contortus and their role in the metabolism of albendazole. (August 2022) - Dimunová, Diana; Navrátilová, Martina; Kellerová, Pavlína; Ambrož, Martin; Skálová, Lenka; Matoušková, Petra
Abstract: Albendazole (ABZ) is an anthelmintic frequently used to treat haemonchosis, a common parasitosis of ruminants caused by the gastrointestinal nematode Haemonchus contortus . This parasite is able to protect itself against ABZ via the formation of inactive ABZ-glycosides. The present study was designed to deepen the knowledge about the role of UDP-glycosyltransferases (UGTs) in ABZ glycosylation in H. contortus . The induction effect of phenobarbital, a classical inducer of UGTs, as well as ABZ and ABZ-sulphoxide (ABZSO, the main active metabolite of ABZ) on UGTs expression and UGT activity toward ABZ was studied ex vivo in isolated adult nematodes. The effect of three potential UGT inhibitors (5-nitrouracil, 4, 6-dihydroxy-5-nitropyrimidine and sulfinpyrazone) on ABZ glycosylation was tested. Pre-incubation of nematodes with ABZ and ABZSO led to increased expression of several UGTs as well as ABZ-glycosides formation in subsequent treatment. Phenobarbital also induced UGTs expression, but did not affect ABZ biotransformation. In the nematode's subcellular fraction, sulfinpyrazone inhibited UGT activity toward ABZ, although no effect of other inhibitors was observed. The inhibitory potential of sulfinpyrazone on the formation of ABZ-glycosides was also proved ex vivo in living nematodes. The obtained results confirmed the role of UGTs in ABZ biotransformation in H. contortus adults and revealed sulfinpyrazone as a potent inhibitor of ABZ glycosylation in this parasite. The possible use of sulfinpyrazone with ABZ in combination therapy merits further research. Graphical abstract: Image 1 Highlights: UDP-glycosyl transferases catalyse biotransformation of benzimidazole anthelmintics. Gene expression of several UGTs in H. contortus is affected by albendazole. The inhibition of UGTs leads to a decrease in the amounts of glycosylated metabolites.